2006
DOI: 10.2320/matertrans.47.935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Characteristics of Plasma Sprayed Hydroxyapatite Coatings

Abstract: Bioactive hydroxyapatite (HA)-coated implants plasma sprayed on Ti6Al4V substrates have been widely used in load-bearing applications because of their biocompatibility and their intimate contact with bone. The improvement of the characteristics of HA coatings is concerned. The purpose of this work was to evaluate corrosion behavior and bond strength of HA coatings after post-deposition heat treatment at 500-700 C. The results indicated that the heat treatment led to recrystallization of amorphous calcium phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The amorphous phase (ACP) dominates the composition in the as-sprayed condition; but controlled crystallization of ACP can be accomplished by post deposition thermal treatments [230]. Porosity is generated within the coating during cooling due to entrapped air, and cracks form due to differential shrinkage.…”
Section: Grain Size and Morphologymentioning
confidence: 99%
“…The amorphous phase (ACP) dominates the composition in the as-sprayed condition; but controlled crystallization of ACP can be accomplished by post deposition thermal treatments [230]. Porosity is generated within the coating during cooling due to entrapped air, and cracks form due to differential shrinkage.…”
Section: Grain Size and Morphologymentioning
confidence: 99%
“…For the present study, the failure mechanism was observed within all the post heating specimens and further clarified for the past studies. 6,28) Figure 7 depicts the overall dependence of bonding strength on heating temperature that can be generalized into two characteristic regions. According to the previous discussion, bonding strength at temperatures lower than 600 C was strongly affected by crystallization, which acted as a main controlling factor.…”
Section: )mentioning
confidence: 99%
“…The most widely used coating method is plasma spray coating, which severely damages the HAp. [18][19][20][21][22]31) BCP and Ti duplex metal-matrix composites can be viewed as a potential alternative but there are also some unique problems associated with using this approach. At higher temperature, Ti is oxidized and TiO 2 and other oxide products are formed.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods of coating Ti have been developed including plasma spraying, dip-spin, electro chemical, etc. [18][19][20][21][22][23] However, coating Ti metal surfaces is complex because the bonding strength of the interface of Ti and BCP is very low. Therefore, it is very difficult to uniformly coat an implant with a complex structure using this technique.…”
Section: Introductionmentioning
confidence: 99%